Social Entrepreneurship Management In Marketer Village In Era Disruption - Puji Novita Sari; Susmy Lianingsih; Yulia Sandra Sari (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
The study aims to explain that the social entrepreneurship management of Marketer Village reviewed from marketing management, operational management, human resource management, and financial management. The four fields of management are the development of management elements that include men, money, machines, methods, materials, and market. Management is an important element in the social entrepreneurship organization so that the business can achieve social missions. The social mission of Marketer Village is to realize the IT literacy community through education and empowerment in the field of digital marketing in District Karangmoncol, Purbalingga. This research is qualitative research with primary data gained through interviews and observations. Based on the results of the research, the manager of Marketer Village focuses on marketing management consisting of product and promotional processes. Operational management aims to generate services in the form of skilled human resources in the field of digital marketing, has mechanisms that control the operation and has a transformation process. Human resource management consists of the development of skills, provision of infrastructure, and compensation. Financial management is made up of funds, and liabilities incurred.